Mapping the risk of interethnic conflict in manokwari through the lens of multicultural politeness understanding - Febriansyah, Riyan; Aristanto, Aristanto; Mahmudah, Hidayatul (Universitas Tanjungpura, 2025)
This study maps the risk of interethnic conflict in Manokwari Regency by focusing on the historical context of conflicts, ethnic distribution, and the understanding of multicultural politeness. A mixed-methods approach was employed through surveys conducted in nine districts and interviews with key informants. Quantitative data were processed using weighted mean scores to produce composite indices per district, categorized into low, medium, and high-risk levels. Findings reveal three clusters: high-risk (West Manokwari, Masni, and North Manokwari), medium-risk (Warmare, South Manokwari, and Prafi), and low-risk (East Manokwari, Tanah Rubuh, and Sidey). Key driving factors include historical legacies of conflict, spatial polarization, and weak interethnic communication. Policy implications emphasize strengthening cross-cultural interaction, designing inclusive public spaces, and providing multicultural communication ethics training for conflict prevention.